Phytochemical evaluation and antimicrobial activity of selected pigmented plants: Garcinia mangostana, Clitoria ternatea, Ardisia colorata var elliptica and Syzygium cumini / Siti Azima Abdul Muttalib, Noriham Abdullah and Nurhuda Manshoor - Abdul Muttalib, Siti Azima; Abdullah, Noriham; Manshoor, Nurhuda (Universiti Teknologi MARA, Negeri Sembilan, 2021)
In recent years, the application of plant extract as natural antimicrobial and colourants in food are gaining interest, concurrently with the increasing reports and consumer awareness on the adverse effect of the synthetic ones. Hence, the objectives of this study were to evaluate the phytochemicals and antimicrobial activity of the selected pigmented plants namely, Garcinia mangostana peel, Clitoria ternatea flower, Ardisia colorata var elliptica fruit and Syzygium cumini fruit. The phytochemicals present in the selected pigmented plants were determined based on the phytochemical screening and liquid chromatography mass spectrometry quadrupole time-of-flight (LC-MS Q-TOF), while antimicrobial activity analysis was carried out using the disc diffusion technique. Phytochemical screening revealed that Garcinia mangostana exhibited the strongest indications for the presence of flavonoid, leucoanthocyanidin, quinone, tannin and anthocyanidin than other pigmented plants studied. Three anthocyanin namely, delphinidin-3-O-glucoside, delphinidin-3-O-galactoside and malvidin-3-O-galactoside was first time identified in A. colorata by LC-MS Q-TOF. The antimicrobial activity analysis showed that, Garcinia mangostana peel exhibited the strongest inhibition on fungi Aspergillus niger and gram-positive bacteria i.e. Bacillus cereus, Bacillus subtilis and Staphylococcus aureus with minimum inhibitory zone of 6.50, 8.50, 6.70, and 7.20 mm, respectively. Therefore, our results suggested that the antimicrobial activity of Garcinia mangostana peel was associated with their specific phenolic compounds. From a practical point of view, Garcinia mangostana peel may be a good candidate for functional foods and pharmaceutical applications.